Evaluation of the Response to Pulpal Sensibility Tests (Cold, EPT) in Anemic and Healthy Women - Maryam Kazemipoor; Mohammad Kazem Vatanchian; Sara Jambarsang; Fatemeh Owlia (Hindawi Limited, 2022)
Introduction. The prevalence of anemia has been reported high in the female population in Iran. Anemia can be asymptomatic or can present in a variety of symptoms, especially when serum Hb values decrease. The present study would assess dental pulp response to cold and EPT sensibility tests in anemic and healthy women. Materials and Methods. One hundred twenty maxillary central incisors belonging to participants aged 18-58 years were included in this survey. 60 patients had anemia (Hb ≤ 12.5) with/without medication (30 in each group) and 60 women as controls had no anemia (Hb > 12.5) with/without medication (30 in each group). Electric and cold pulpal sensibility tests were performed for all teeth. Statistical analysis was performed with t-student, Chi-square test, and two-way ANOVA. The significance level was set as p<0.05. Results. According to the results of this study, the mean value of hemoglobin in anemic and healthy women was 11.5 and 14.08 g/dl, respectively. The mean value of response to EPT in anemic women with and without medication was 3.21 and 3.14, respectively. The mean value of response to EPT in healthy women with and without medication was 3.81 and 3.58 g/dl, respectively. The mean value of time delay response to cold test was 3.03 and 2.82 s in anemic patients with/without medication. Also, the mean value of time delay response to cold test was 2.80 and 2.93 s in healthy women with/without medication. The pulpal responses to EPT tests had significant differences between anemic and healthy women (p=0.043). There were no significant differences between anemic and healthy women considering time delay response to the cold test (p=0.077). Conclusion. Based on the results of the present study, tooth response to the EPT  sensibility test may alter in anemic patients despite medication. The evidence from this preliminary study suggests that peripheral neuropathy in anemic patients could affect pulpal sensibility tests.